2008
DOI: 10.1111/j.1471-0307.2008.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of bacteriocin‐producing Lactobacillus plantarum, Enterococcus faecium and Lactococcus lactis ssp. lactis as adjunct starter in Minas Frescal cheesemaking

Abstract: The antimicrobial and technological characteristics of three bacteriocinogenic cultures used as adjunct starters in Minas Frescal cheese were investigated. The cheeses were manufactured with 1% commercial lactic starter and 0.5%Lactococcus lactis ssp. lactis ATCC 11454, Lactobacillus plantarum ALC 01 or Enterococcus faecium FAIR‐E 198. The cheeses were then artificially inoculated with Listeria monocytogenes Scott A, Staphylococcus aureus ATCC 27154 and Bacillus cereus K1‐B041 and stored for 21 days at 8°C. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
(41 reference statements)
0
16
0
1
Order By: Relevance
“…However, because of the potential development of resistance, it was concluded that a pediocin AcH should not be used continuously over a long time in a production line. On the contrary, in Minas Frescal cheese, the Lp ALC 01 employed had not a significant effect on the counts of Lm (Nascimento, Moreno, & Kuaye, ). These differences in the efficacy of Lp could be attributed to the difference in the strains and kinds of antagonistic compounds that were produced.…”
Section: Resultsmentioning
confidence: 96%
“…However, because of the potential development of resistance, it was concluded that a pediocin AcH should not be used continuously over a long time in a production line. On the contrary, in Minas Frescal cheese, the Lp ALC 01 employed had not a significant effect on the counts of Lm (Nascimento, Moreno, & Kuaye, ). These differences in the efficacy of Lp could be attributed to the difference in the strains and kinds of antagonistic compounds that were produced.…”
Section: Resultsmentioning
confidence: 96%
“…(2002) who showed that Enterococcus faecium FAIR‐E 198 was able to produce a bacteriocin when incubated in skimmed milk, but no enterocin activity was observed when fermentations were performed in skimmed milk in the presence of rennet and CaCl 2 and when the strain was used as adjunct starter in Feta cheesemaking. Nascimento et al. (2008) showed that no antimicrobial effect was observed against Listeria monocytogenes Scott A and S. aureus ATCC 27154 in Minas Frescal cheese manufactured with the addition of bacteriocin‐producing adjunct cultures Lac.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteriocin activity in cheese may be affected by adsorption to the caseins, by the action of proteases and rennet, or by adsorption to the fat molecules or low diffusion capacity in the cheese matrix (Nascimento et al. 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Our dynamic tertiary model to estimate the growth of L. monocytogenes considering environmental parameters in this Brazilian traditional soft cheese represents an important advance. Prior studies have evaluated only the presence or absence of the pathogen in Minas frescal cheese (Brito et al, 2008;Pinto et al, 2011;Silva et al, 1998) or the capacity of a compound or microorganism to inhibit its growth during processing or storage (Malheiros et al, 2012;Naldini et al, 2009;Nascimento et al, 2008;Silva et al, 2014). Campagnollo et al (2018) have modeled the fate of L. monocytogenes and LAB with anti-listerial activity in Minas soft cheese using only primary models (Baranyi and Roberts, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed L. monocytogenes behavior in Minas fresh cheese during processing and shelf-life (Malheiros et al, 2012;Naldini et al, 2009;Nascimento et al, 2008;Silva et al, 2014), but only Campagnollo et al (2018) used primary predictive models to estimate the growth parameters of this pathogen. No previous work appears to have applied either competition models or dynamic tertiary models to describe the kinetics of L. monocytogenes in Brazilian cheeses.…”
Section: Introductionmentioning
confidence: 99%